Defibrotide Stimulates Expression of Thrombomodulin in Human Endothelial Cells - Zhou, Quansheng; Chu, Xiaohong; Ruan, Changgeng (Thrombosis and Haemostasis, 1994)
Cultured human umbilical vein endothelial cells were incubated with defibrotide at concentrations of 0, 5, 50 and 500 jxg/ml for 4 and 24 h respectively. Thrombomodulin activity and molecules on the surface of the cells were determined by chromogenic assay and radioimmunoassay, thrombomodulin antigen in endothelial cells and in conditioned medium of the cells was measured by immunoradioassay. Thrombomodulin mRNA within the cells was analysed by slot blot. After 24 h of incubation, the activity and molecules of thrombomodulin on the surface of endothelial cells, as well as the antigen and mRNA of thrombomodulin in the cells were significantly increased in a dose dependent manner. However, the level of thrombomodulin antigen in conditioned medium was about equal to that of the control. Our data indicate that defibrotide stimulates expression of thrombomodulin in human endothelial cells. These beneficial effects may play a role in antithrombotic activity of defibrotide.